Physicochemical Properties, Chemical Compositions and Antioxidant Activities of Rhizome Oils from Two Varieties of Kaempferia galanga - I Wayan Muderawan; I Wayan Mudianta; Ni Wayan Martiningsih (Universitas Gadjah Mada, 2022)
Kaempferia galanga is a tropical plant with an impressive range of food and medicinal uses. This study, therefore, investigated the variation in yields, physicochemical properties, chemical compositions, and antioxidant activities of rhizome oils from two K. galanga varieties, K. galanga bigger rhizomes (V1) and K. galanga smaller rhizomes (V2), isolated by steam distillation (S) and maceration (M) techniques. The air-dried rhizomes' oil contents were found to be 2.81±0.09% (SV1O), 7.93±0.20% (MV1O), 3.60±0.10% (SV2O), and 8.76±0.22% (MV2O), respectively. From the GC-MS analysis, the SV1O, MV1O, SV2O, and MV2O samples contain 49, 48, 61, and 56 compounds, respectively. Furthermore, ethyl trans-p-methoxycinnamate was the most prevalent chemical constituent in four oils with a percentage contribution of 43.37% (SV1O), 60.62% (MV1O), 24.92% (SV2O), and 57.17% (MV2O). Several long-chain alcohols (6Z,9Z-pentadeca-6,9-dien-1-ol, 9E,12E-octadeca-9,12-dien-1-ol, heptadecan-1-ol), aldehyde (Z-octadec-9-enal), carboxylic acids (4-(4-methoxyphenyl)oxane-4-carboxylic acid, hexadecanoic acid), diterpene sandaracopimaradiene, steroid ergosterol, and alkaloid 2-imino-3-(3-nitrophenyl)-1,3-thiazolidin-4-one, were also identified in K. galanga rhizome oils isolated by maceration method. In addition, all oils showed high antioxidant activities with the IC50 values of 86.10±1.51, 85.24±1.48, 89.19±1.72, and 86.49±2.03 μg/mL for SV1O, MV1O, SV2O, and MV2O, respectively.